2022
DOI: 10.1063/5.0100991
|View full text |Cite|
|
Sign up to set email alerts
|

Thermoelectric transport contribution from topological surface states vs 2D-electron gas in 10 nm Bi2Se3

Abstract: Topological surface states (TSSs) coexist with a rapidly formed two-dimensional electron gas (2DEG) at the surface of Bi2Se3. While this complex band structure has been widely studied for its interactions between the two states in terms of electrical conductivity and carrier density, the resulting thermopower has not been investigated as thoroughly. Here, we report measurements of the temperature dependent Seebeck coefficient ( S) and electrical conductivity ( σ) on an undoped 10 nm thin Bi2Se3 film over the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In 3D TIs, the thermoelectric properties of surface states have been extensively investigated [34][35][36][37][38][39][40][41][42][43]. In experiment, Sun et al found that the thermoelectric figure of merit(ZT) of Bi 2 Se 3 can be enhanced by reducing the grain size of bulk due to increased topologically conducting surfaces [44].…”
Section: Introductionmentioning
confidence: 99%
“…In 3D TIs, the thermoelectric properties of surface states have been extensively investigated [34][35][36][37][38][39][40][41][42][43]. In experiment, Sun et al found that the thermoelectric figure of merit(ZT) of Bi 2 Se 3 can be enhanced by reducing the grain size of bulk due to increased topologically conducting surfaces [44].…”
Section: Introductionmentioning
confidence: 99%